(untitled) (Universal International Scientific Journal, 2026)
In this study, the structural properties of the silkworm cocoon (Bombyx mori L.) and the hexane-defatted cocoon were studied. The sample was extracted using the Soxhlet method, and the residual biomaterial was examined by SEM and IR analyses. The results showed an increase in surface porosity and the presence of functional groups characteristic of protein nature.